Upaya Guru Akidah Akhlak dalam Menanamkan Karakter Tanggung Jawab pada Siswa Kelas VIII di Mts Hidayatul Mubtadiin Desa Sidoharjo Kecamatan Jati Agung Lampung Selatan - Yumida Yumida; Riskun Iqbal; Ayu Aristika (Journal on Education, 2024)
The purpose of this research is 1) to find out how the moral aqidah teacher's efforts are in instilling the character of responsibility in students at MTs Hidayatul Mubtadiin Sidoharjo Jati Agung, South Lampung Regency. 2) to determine the inhibiting and supporting factors in instilling the character of responsibility in class VIII students at MTs Hidayatul Mubtadiin. This research method uses a qualitative approach. The method used in this research is observation, interviews, documentation. The results of the research show that the efforts of moral aqidah teachers in instilling the character of responsibility in students at MTs Hidayatul Mubtadiin are understanding that students' characters do not develop at the same speed, giving assignments, grouping students, modifying and enriching materials, using varied procedures, using character education methods. varied, and strive for student involvement in various characterful activities. The driving factors in instilling the character of responsibility in students are family factors, family factors, and environmental factors. Meanwhile, the inhibiting factors in cultivating the character of responsibility are family factors and environmental factors.